Reproducing Chinese Culture in Diaspora: Sustainable Agriculture and Petrified Culture in Northern Thailand - Huang, Shu-min, (Lexington Books, 2009)
Reproducing Chinese Culture in Diaspora discusses how a group of anti-communist Chinese exiles from Yunnan Province have managed to establish a rural livelihood in Thailand's northern hills over the past half century. When faced with the seemingly invincible Communist forces that were sweeping across the Mainland, these nationals retreated in 1949 or shortly thereafter to the Golden Triangle that sits astride the borders of Burma, Laos, and Thailand in voluntary exile. This book mainly concerns their hardships as they have struggled to carve out a new life along with their attempts to find an agricultural identity in the area. Initially gaining power as drug traffickers and narco-kings, the Yunnan exiles have transformed into sustainable farming leaders. Yet, despite their success in establishing themselves in Thailand, their community is facing a steep decline that threatens their long time survival. Part of their rationale in leaving communist China in search of a new settlement in the Golden Triangle, the exiles sought to protect Chinese traditions and ideals in the face of what they felt was Western influence. Yet, in their attempts to maintain their traditions, they've drifted to the opposite extreme, treating those traditions as sacrosanct and adhering to them rigidly. As a result, many of the younger generations are fleeing the communities from this 'cultural petrification,' and those who stay openly challenge the authoritarian old guard in a desire to modernize. This clash of old vs new severely strains a prosperous yet fragile community, clouding its future in uncertainty.